ANALISIS KELAYAKAN FINANSIAL USAHATANI SAYURAN SISTEM HIDROPONIK DI KOTA KUPANG - Here, Arif Alexander; Kapioru, Charles; Siubelan, Yacobus C.W. (Undana Press, 2023)
This research was conducted in the city of Kupang on the St. Hydroponic, Pelangi Hidroponik, J. I. Hydroponic and Alexa Garden farming businesses. The aims of this study were: 1) To know the motives or reasons for farming vegetables with a hydroponic system, 2) To know the management of vegetable farming with a hydroponic system in Kupang City, 3) To know the financial feasibility of vegetable farming with a hydroponic system in Kupang City. The data used in this study uses primary data and secondary data. The research method uses analytical tools: R/C Ratio, Break Even Points (BEP) and Payback Period (PP). Calculating software using Microsoft Excel and a calculator. The results of this study indicate that: 1) based on the results of the research. The motives or reasons for the four hydroponic system vegetable farming in the city of Kupang: for hobbies, to fill spare time, high curiosity and educate the public about consumption of pesticide-free vegetables. 2) based on the results of management research on the management of the four hydroponic system vegetable farming managers in Kupang City, namely: a) planning, b) organizing, c) implementation and, d) supervision. 3) based on the results of the analysis of the financial aspects of hydroponic system vegetable farming in the city of Kupang on St. Hydroponic, Pelangi Hidroponik, J. I. Hydroponic and Alexa Garden farming businesses are feasible to cultivate.